Rol de la hormona del crecimiento en la función ovárica de la vaca lechera - Leiva, C.J. (2021)
Growth hormone is recognized as a key endocrine regulator of postnatal growth and production\nin dairy cattle. However, it is currently known that this hormone also affects reproduction in these\nanimals. Ovarian function in cattle is controlled by intraovarian control mechanisms that, concomitantly with endocrine signals, coordinate recruitment, selection and follicular growth. Although the role of gonadotropins in stimulating follicular growth and differentiation is clear, particularly during the final stages of maturation, growth hormone also plays an important modulating role, since it exerts multiple direct and indirect effects on the ovary, acting on steroidogenesis, folliculogenesis and oocyte maturation. Any advances in understanding intraovarian regulatory mechanisms will be helpful in the design of new approaches to manipulating ovarian function and improving fertility in dairy herds.